Contrastive analysis of English and Indonesian adverbs - Auni, Luthfi; Manan, Abdul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study focuses on contrastive analysis of the characteristics and features of adverbs in English and Indonesian languages. This study explores all similarities and differences of adverbs according to their forms, formations, meanings and positions in both languages thoroughly and accordingly predict what sorts of errors the Indonesian learners of English may encounter. This research uses descriptive method by using library research in which all data are collected from linguistics books from both languages. The findings show that there are similarities and differences almost in all aspects of adverbs in both languages. (1). Both languages have two similar forms, as origin and derivative. But in Indonesian, the original and derivative ones can be classified again into reduplication word. (2). The formations of adverbs in both languages use different affixation systems as inflection and derivation. Indonesian uses various affixes such as prefixes, suffixes and confixes, while English uses only kinds of affixes as prefix and suffix. In forming adverbs from adjectives, English uses a suffix ‘-ly’, and a prefix ‘a-‘, meanwhile most of the Indonesian adverbs have the same form as adjectives or without any addition of affixes. Referring to adverbs derived from verbs, Indonesian ones may be formed through reduplicating the base form of the verbs, while English does not have this system. The formation of adverbs derived from nouns, English uses some suffixes such as, -ly, -ward(s), -ways, -wise, and a prefix, a-. Meanwhile Indonesian uses only one prefix ‘se-, one suffix –nya’ and by reduplicating the base form of the noun (e.g., hati becoming hati-hati), it is not in English ones. (3). In terms of their meanings, even though both English and Indonesian are alike, a great difference appears that several words called auxiliaries verbs in English and some English verbs such as, like, want, and wish, etc. have different word classes, concept and function in both languages. Those auxiliaries’ words and verbs are basically real adverbs as qualifiers in Indonesian. (4). Referring to adverb positions, generally, Indonesian adverbs are more mobile in sentences, meanwhile, English ones have certain common positions except some words should be placed permanently. These differences of adverbs in English and Indonesian are identified as problems caused by language interference for Indonesian students. Consequently, the results of this extensive research may be useful for teachers, students, curriculum development and materials of teaching.